2019
DOI: 10.48550/arxiv.1908.00389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Holographic bounce

Shin'ichi Nojiri,
Sergei D. Odintsov,
Emmanuel N. Saridakis

Abstract: We investigate the bounce realization arising from the application of the holographic principle in the early universe, inspired by its well-studied late-time application. We first consider as Infrared cutoffs the particle and future event horizons, and we show that the decrease of the horizons at early times naturally increases holographic energy density at bouncing scales, while we additionally obtain the necessary null energy condition violation. Furthermore, adding a simple correction to the horizons due to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Various investigations in the past decades have demonstrated that even simple modifications of gravitational Lagrangian with respect to the standard Einstein-Hilbert action, while leaving all other physical assumptions of Einstein's general relativity intact, can prevent the appearance of the big-bang singularity [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Also, in higher curvature gravity theories some important non-singular investigations have been done in Gauss-Bonnet higher curvature gravity [22][23][24] and in f (R) gravity theories [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Various investigations in the past decades have demonstrated that even simple modifications of gravitational Lagrangian with respect to the standard Einstein-Hilbert action, while leaving all other physical assumptions of Einstein's general relativity intact, can prevent the appearance of the big-bang singularity [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Also, in higher curvature gravity theories some important non-singular investigations have been done in Gauss-Bonnet higher curvature gravity [22][23][24] and in f (R) gravity theories [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, it inevitably suffers from the initial singularity problem [5]. Due to this concern, bouncing cosmology, which addresses this issue with a non-zero minimal size of universe, has been extensively studied such as in [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. As a promising alternative to inflation, it can also resolve the horizon and flatness problems and generate a nearly scale-invariant curvature spectrum [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations with application to holographic dark energy in the late-time cosmology were presented in several papers [4][5][6][7][8][9][10][11][12][13]. The holographic principle can be realized also in the early universe, obtaining inflation [14], and a cosmological bounce [15], having a holographic origin. It has been shown that the application of the theory of holographic dark energy in the late-time universe is consistent with astronomical observations [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%